Study of the phenolic compound profile and antioxidant activity of human milk from Spanish women at different stages of lactation: A comparison with infant formulas. (March 2021) - Sánchez-Hernández, Silvia; Esteban-Muñoz, Adelaida; Samaniego-Sánchez, Cristina; Giménez-Martínez, Rafael; Miralles, Beatriz; Olalla-Herrera, Manuel
Graphical abstract: Highlights: Twenty-six phenolic compounds in human milk were quantified. More than half of the quantified phenolic compounds were phenolic acids. Human milk has a higher antioxidant capacity than infant formulas. The antioxidant activity of human milk slightly varied during lactation. Abstract: Human milk (HM) has been proven to have important and essential antioxidant properties to counteract infant susceptibility to oxidative stress. Phenolic compounds are secondary metabolites which come from plants and are potent natural antioxidants. The ultra-performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS) method used in the present study allowed the quantification of 26 phenolic compounds (ten hydroxybenzoic acids, seven hydroxycinnamic acids, four flavonoids, three hydroxybenzaldehydes and two other polyphenols) in HM samples at different stages of lactation (colostrum, transitional milk and mature milk) and infant formulas (IF). Many of the phenolic compounds identified have been reported to be present in HM for the first time. The total phenolic compound content (TPC) was quantified using the Folin assay and the antioxidant activity (AC) was evaluated with the DPPH, ABTS and FRAP assays. Significant differences were evidenced between HM and IF. HM from mothers with an adherence to a Mediterranean diet contained twice as many individual phenolic compounds as infant formulas, with a higher proportion of hydroxybenzoic acids. Conversely, IF showed a higher proportion of hydroxycinnamic acids. Overall, the antioxidant activity of HM showed small variations during lactation.